Experiential and Textual Functions Analysis of Minangkabau Song Lyric “Taragak Pulang” - Uswar, Yenita; Harahap, Dina Irmayanti (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2024)
This research investigates the results of SFL (Systemic Functional Linguistics) study on the Experiential and Textual functions in the Minangkabau Song Lyric “Taragak Pulang”. The primary goal of this research is to describe many sorts of Processes, Participants and Circumstances featured in experiential function in that song, and also to analyze the Theme and Rheme in Textual Function. The research design of this analysis is a descriptive qualitative method. This research aims to analyze the experiential function and textual Function of sentences as an exchange in the Minangkabau Song Lyric "Taragak Pulang". The data source used in this research is the documentation of the data research paper. The result of this research in experiential function is found that in experiential function, there were material, mental and relational processes, with the dominantly used mental process. In textual function, it was found marked simple theme, unmarked simple them, marked multiple theme and unmarked multiple themes, which is marked simple theme is dominantly found in that song lyric. Marked themes were identified by given as previous information and new as last information. From this result, these two metafunctions are concerned with how humans engage with one another through language from the Minangkabau song lyric “Taragak Pulang”.